Winter barley resistance to cold and productivity - Ярчук, І. І.; Божко, В. Ю.; Войт, В. А. (Scientific Progress & Innovations, 2012)
Results of the research of winter barley reaction on the sowing terms and seeding rates depending on hydrothermal conditions of the year are given. Great attention is paid to the research of the dependence of the sowing terms and seeding rates on the winter barley resistance to cold. It has been established that variety Cinderella wintered better than the other varieties. The domestic variety Osnova had the greatest productivity in sowing in the optimal term for the subarea in the beginning of the third decade of September (22 Sept) with seeding rate 3.5 million germinable seeds per a hectare.